Subungual exostosis of the great toe: A case report - Kafle, Pradeep; Rijal, Nishchal; Pandey, Ashish Kumar (Journal of Kathmandu Medical College, 2020)
Subungual exostosis is typically a rare benign, acquired tumor of cartilaginous bone occurring on the medial surface of the distal hallux of toes or fingers. These are usually associated with secondary changes such as elevation of the nail plate, ulceration or subungual hyperkeratosis and hyperpigmentation. On histological examination, the lesion consists of mature bone at the base with proliferating fibrocartilaginous cap. A 14-year-old male presented with a solitary firm swelling gradually increasing in size for three months on the distal part of the right great toe. On physical examination, a firm, non-tender, non-mobile, whitish nodule was noted in the distal dorsomedial aspect of the right great toe distorting the adjacent nail. Radiographs demonstrated a dorsal bony outgrowth that was continuous with the distal phalanx. Excisional biopsy was done and on histopathological examination, a characteristic trabecular pattern of mature bone covered with a hyaline and fibrocartilaginous cap was seen. There was lack of true anaplasia, thereby confirming the diagnosis of subungual exostosis. There was no recurrence over six months. This topic is underrepresented in the orthopaedic literature, because many of the important clinical series have been published in journals from other branches of medicine i.e. mainly by dermatologists and pathologists. This reflects the fact that the condition is treated by many kinds of non-orthopaedic providers. We, as orthopaedic surgeons, must be careful while evaluating lesions of distal phalanges, always keeping in mind the possibility of subungual exostosis. Radiographs are helpful in diagnosis but confirmation can be done by histopathological examination. En bloc excision with minimal nail plate deformation can help prevent recurrence or deformity.